A case of lipoma of lateral anterior neck treated with surgical enucleation - Francesco Grecchi; Ilaria Zollino; Valentina Candotto; Francesco Gallo; Giuseppe Rubino; Raffaella Bianchi; Francesco Carinci (Wolters Kluwer Medknow Publications, 2012)
Lipoma arise in almost 50% of all soft tumours. The neck lipomas are rare tumours that may present as painless masses with slow growth, in the lateral portions of the neck. Some lipomas, such as the one studied in our case, grow deep in the subcutaneous tissue, in close contact with muscles. Here, we report a case of lipoma extending from pre-tragal region up to the ascending branch of the mandible in a 62 year old man, treated with enucleation. The inferior margin of lipoma involved the pharyngeal and the superior margin was achieved by the top of the skull base. The mass of lipoma caused breathing difficulties in the patient, preventing regular sleep. No complication was recorded in the post-operative period and no further surgery was performed. The complete resolution after one year's follow-up, together with the rarity of the anatomical site, makes this case worthy of description. A correct diagnosis facilitated removal of this lesion with a surgical method.